On the brittle fracture characteristics of lamella walls of ice-templated sintered alumina scaffolds and effects of platelets. (September 2017) - Ghosh, Dipankar; Banda, Mahesh; Akurati, Sashanka; Kang, Hyungsuk; Fakharizadeh, Vivian O.
Abstract: We attempted to develop a phenomenological understanding of the evolution of the fracture events within fine-grained lamella walls of partially deformed ice-templated sintered Al2 O3 scaffolds and revealed the effects of the platelets on the crack propagation characteristics. Detailed microstructural analyses suggest that intergranular cracks within the walls evolved at two orientations, parallel and perpendicular to the loading direction. We proposed probable mechanisms including one based on the so-called wing-crack model to rationalize the observed crack orientations. We presented crack propagation behavior in lamella walls in presence of the platelets and discussed the effects in terms of the crack deflection mechanism. Graphical abstract: